Haar Wavelet Operational Matrix Method for Fractional Oscillation Equations - Umer Saeed; Mujeeb ur Rehman (International Journal of Mathematics and Mathematical Sciences)
We utilized the Haar wavelet operational matrix method for fractional order nonlinear oscillation equations and find the solutions of fractional order force-free and forced Duffing-Van der Pol oscillator and higher order fractional Duffing equation on large intervals. The results are compared with the results obtained by the other technique and with exact solution.